Advancements in multiscale oil palm fiber composites: Manufacturing techniques, performance evaluation, and industrial applications - Siddiqui, Vasi Uddin; Sapuan, SM; Isah, Aliyu; Yusuf, J.; Khan, Abir (Elsevier, 2024)
The increasing demand for eco-friendly solutions for industrial applications has garnered significant interest in oil palm fiber (OPF) as a reinforcement in polymer composites. This review integrates concurrent knowledge on OPF and its various byproducts having potential industrial applications. The manufacturing techniques of OPF reinforced polymer composites and their mechanical and thermal properties have been discussed meticulously. Different performance enhancement strategies such as maleic anhydride grafting and benzoylation of the OPF composites have also been reviewed. Furthermore, characterization techniques involving the structural and functional attributes of the OPF composites have been elucidated. Findings indicate that OPF composites are well suited for automotive and construction applications, contributing to waste valorization and eco-efficiency. This review article serves as an extensive source of information and is highly valuable for researchers seeking to harness the potential of OPF reinforced polymer composites.